EduNexa shines at CITREX 2025: Muhammad Amir wins ‘Best of the Best Student’ Award with Digital Learning Innovation - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 23 June 2025 – A proud achievement was recorded by Muhammad Amir Mohamed Ali, a final-year student of the Bachelor of Computer Science (Software Engineering) from the Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) when he was named the recipient of the Best of the Best Student Award at the Creative and Innovative Technology Research Exposition (CITREX) 2025 recently.